Visuomotor and audiomotor reaction time in elite and non-elite badminton players - Kaplan, D. S.; Akcan, F.; Cakir, Z.; Kilic, T.; Yildirim, C. (European Journal of Physical Education and Sport Science, 2017)
The ability to quickly perceive appropriate motor response is essential in the badminton sport under the critical time pressure. This study aimed to evaluate the visual and auditory reaction time, speed, anaerobic power and vertical jump between elite and non-elite badminton athletes. With this purpose, various anthropometric measurements, hexagonal obstacle test, vertical jump test, anaerobic power measurement and auditory and visual reaction time tests were performed to the elite and non-elite athletes. When auditory reaction time, vertical jump and anaerobic power measurements were evaluated, there was no significant difference between the elite and non-elite groups, but it was noticed that there was a significant differences in quickness and visual reaction time in favor of elite athletes. It is also seen that speed and visual reaction time have a positive effect on badminton athletes are able to get to the high performance level in other literature information. For this reason, it has been thought that training programs designed for badminton athletes by considering these physiological parameters and training systems designed to increase the reaction time may be beneficial.